Altertavlerne fra Skjern Kirke ved Nørreå: Om altertavler, våbenskjolde og hovedgårde - Vellev, Jens (Kirkehistoriske Samlinger, 2011)
Summary Skjern Church, a small church located north of the Nørreå stream between Viborg and Randers, contained two late medieval wing altarpieces until the end of the nineteenth century. On the altar table was a large altarpiece from c. 1525. On the north wall of the choir hung a smaller one from c. 1475. The small altarpiece was given to Viborg Museum in 1891 and immediately placed in the exhibition. The coats of arms for the Krognos and Rosenkrantz families on the side wing of the small altarpiece identify the contributors as Otte Nielsen Rosenkrantz (c. 1395-1477) and his wife Else Krognos (c. 1380-1470). The ancient literature on Skjern Church and Skjern Castle often mentions that the piece was originally in the castle chapel on manor called »Skjern Castle«, which was located in the meadow south of the Nørreå stream, with a view of the church towards the north. Today, all that remains of the old manor are grassy earthworks. On one of the side wings of the altarpiece, a picture of Christ’s birth, now almost gone, displayed a fortress in its scene. Before almost completely peeling off, the motif was drawn by the architect Martin Borch (1852-1937). His drawing is often reproduced in the literature, accompanied by text indicating that this was an artistic rendition of Skjern Castle. It is now clear that the altarpiece was originally made for an entirely different church, Tirstrup Church located on southern Djursland. The couple had the church built in 1465 near their manor called Bjørnholm, located a couple of kilometres away. So the painted fortress motif on the altarpiece should rather be linked to this manor – if it is at all reasonable to suggest that the painter based his work on the actual building. Otte Nielsen’s grandchild, Niels Eriksen (d. 1516) was married to Birgitte Thott (d. 1528). She donated a new altarpiece to Tirstrup Church in 1522, and on this occasion the old altarpiece from c. 1475 was probably brought to Skjern. She often stayed at »Skjern Castle« at this point, and around 1525 she also donated a new altarpiece to the church there. It is the one still in place on the church altar. These interpretations of the location, dating and donation conditions of the altarpieces are mostly based on the more or less well-preserved coats of arms still located on the preserved altarpieces.